Effectiveness of different booster vaccine combinations against SARS-CoV-2 during a six-month follow-up in Mexico and Argentina - Garza-Silva, Arnulfo; Rivera-Salinas, Diego; Rivera-Cavazos, Andrea; Fernández-Chau, Iván Francisco; Cepeda-Medina, Andrea Belinda; Morales-Rodríguez, Devany Paola; Barco-Flores, Irene Antonieta; Sanz-Sánchez, Miguel Ángel; Acciardi, Cecilia; Paez-Bo, Graciela; Teixeira, Mauro M.; Azzolini, Elena; et al. (Frontiers in Immunology, 2024)
Given the limited number of patients in Latin America who have received a booster dose against the COVID-19, it remains crucial to comprehend the effectiveness of different vaccine combinations as boosters in real-world scenarios. This study aimed to assess the real-life efficacy of seven different vaccine schemes against COVID-19, including BNT162b2, ChAdOx1-S, Gam-COVID-Vac, and CoronaVac as primary schemes with either BNT162b2 or ChAdOx1-S as booster vaccines. In this multicentric longitudinal observational study, participants from Mexico and Argentina were followed for infection and SARS-CoV-2 Spike 1-2 IgG antibodies during their primary vaccination course and for 185 days after the booster dose. A total of 491 patients were included, and the booster dose led to an overall increase in the humoral response for all groups. Patients who received BNT162b exhibited the highest antibody levels after the third dose, while those with primary Gam-COVID-Vac maintained a higher level of antibodies after six months. Infection both before vaccination and after the booster dose, and Gam-COVID-Vac + BNT162b2 combination correlated with higher antibody titers. The sole predictor of infection in the six-month follow-up was a prior COVID-19 infection before the vaccination scheme, which decreased the risk of infection, and all booster vaccine combinations conveyed the same amount of protection.